HYDROCEPHALUS – PATHOPHYSIOLOGY, CLASSIFICATION, AND CLINICAL MANIFESTATIONS - Khakimov M.N., (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Hydrocephalus is a neurological disorder characterized by abnormal accumulation of cerebrospinal fluid (CSF) within the ventricular system, leading to ventricular dilation and increased intracranial pressure. It affects individuals of all ages, from neonates to the elderly, and may arise from congenital or acquired causes. This article reviews the pathophysiological mechanisms, classification systems, clinical features, and complications associated with hydrocephalus.